1991
DOI: 10.1152/jn.1991.66.1.293
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid receptor-mediated transmission in geniculocortical and intracortical pathways within visual cortex

Abstract: 1. A preparation of turtle (Chrysemys picta and Pseudemys scripta) brain in which the integrity of the intracortical and geniculocortical pathways in visual cortex are maintained in vitro has been used to differentiate the excitatory amino acid (EAA) receptor subtypes involved in geniculocortical and intracortical synapses. 2. Stimulation of the geniculocortical fibers at subcortical loci produces monosynaptic excitatory postsynaptic potentials (EPSPs) in visual cortical neurons. These EPSPs are blocked by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Previous ligand binding and electrophysiological studies have demonstrated the presence of functional AMPA and NMDA receptors in the forebrain of turtles, but no specific information has been available on the regional or cellular localization of NMDA and AMPA subunits in the basal ganglia of reptiles [Young et al, 1990;Larson-Prior et al, 1991;Blanton and Kriegstein, 1992]. In the present study we have characterized the distribution of several AMPA and NMDA receptor type subunits in the basal ganglia of turtles.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previous ligand binding and electrophysiological studies have demonstrated the presence of functional AMPA and NMDA receptors in the forebrain of turtles, but no specific information has been available on the regional or cellular localization of NMDA and AMPA subunits in the basal ganglia of reptiles [Young et al, 1990;Larson-Prior et al, 1991;Blanton and Kriegstein, 1992]. In the present study we have characterized the distribution of several AMPA and NMDA receptor type subunits in the basal ganglia of turtles.…”
Section: Discussionmentioning
confidence: 77%
“…Although we did not demonstrate the presence of NMDAR1 receptor subunits in turtle brain, several considerations argue that such subunits are present and likely to be found in the same neurons that we found to possess NMDAR2A/B subunits. First, functional NMDA receptors cannot form in the absence of the NMDAR1 subunit, and physiological and ligand binding studies demonstrate the presence of functional NMDA receptors in turtles [Young et al, 1990;Larson-Prior et al, 1991;Blanton and Kriegstein, 1992]. Secondly, an NMDAR1 subunit has been demonstrated in chick [Kurosawa et al, 1994] and in a lizard species [Rodger et al, 1999], as well as in Xenopus laevis and a teleost species [Soloviev et al, 1997;Dunn et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the basic anatomo-functional features of the mammalian cortex are shared by the much simpler turtle cortex [Desan, 1984;Connors and Kriegstein, 1986;Kriegstein and Connors, 1986;Larson-Prior et al, 1991;Reiner, 1993]. As in mammals, the reptilian cortex receives dense projections from extrathalamic sources.…”
Section: Introductionmentioning
confidence: 99%